Workshop Parenting Mendidik Anak dalam Membentuk Karakter Religius di Era Digital - Fahrurrozi Fahrurrozi; Farida Isroani; Ulfa Ulfa; Nurlaela Nurlaela (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
This program aims to introduce the world of computing to guardians, and teaches them to have the choice to prepare. Young people face the rapid progress of innovation by applying Islamic traits to children. This Business Program aims to provide preparation skills and provide knowledge to guardians regarding correct Islamic parenting patterns for children in old age. Starting from this problem, then, at that time, what do guardians of Islamic boarding school students need to do to prevent and survive the bad consequences of the world? Computerization is developing Digital Resilience in children. Advanced Resilience is the capacity to control the possible risks of an internet-based world by developing virtue in children. This work must be made possible by instilling great Islamic qualities and character in young people.